INSTITUTIONAL COORDINATION OF FLOOD CONTROL AT MEDAN CITY IN MEBIDANGRO COOPERATION SCHEME - Thamrin, Muhammad Husni; Ridho, Hatta; Nasution, Faiz Albar (Universitas Padjadjaran, 2021)
Flood management system in Medan City is very poor, because there is no institutional coordination resulting from sectoral egos. Effective institutional coordination in urban flood management is needed. Condition is based on problem of flooding in Medan City which has not been effectively implemented, so an alternative solution for integrated urban flood management is needed. Purpose of this research is to explain implementation of flood control policies in Medan City and how coordinate flood control institutions in Medan City in Mebidangro cooperation scheme. This type of qualitative research with descriptive methods is used in this research. Primary data collection techniques with deep interviews through FGD activities with stakeholders. In addition, secondary data is collected by citing journals, books, documents, online media, and other materials support research. Data analysis techniques are carried out through data reduction activities, data display and drawing conclusions. Results showed implementation Presidential Regulation No. 62 of 2011 on flood control in Medan City has not been optimally implemented. Condition is influenced lack of understanding authority and lack of coordination between related agencies to safeguard river basins, river norms and establish primary drainage channels. In addition, coordination of Medan City flood control institution in Mebidangro cooperation scheme has been carried out in a procedural manner. However, actualization still requires visionary leadership and command to support success program.